Natural resources and technology - on the mitigating effect of green tech - Tobias Wendler; Daniel Töbelmann; Jutta Günther (ZBW - Leibniz Information Centre for Economics, 2021)
Drawing upon the literature on environmental innovation and social metabolism, this paper investigates whether technology can lessen the problem of scarce natural resources. We focus on fossil and biomass materials as important resources for production and consumption. Utilizing a dynamic panel approach, the paper empirically analyses whether environmental innovations reduce the usage of biomass and fossil materials at the national level. Our results suggest that there is no consistent mitigating effect of green technology. Rather more, substantial heterogeneity in technology effects can be found between different types of resources. For biomass, no significant technology effects are found. Fossil materials are saved by innovations in recycling as well as by new production and processing technologies. Further, substitutional dynamics of fossil energy carriers are of major importance
Keywords: Q01; Q55; Q56; Q58; 330; Dynamic Panel; Environmental Innovation; Material Flows; Patent Data; Social Metabolism; Sustainable Development